Arginine-loaded mesoporous silica nanoparticles modified 3D-printed nanocomposite denture base resin with improved mechanical and antimicrobial properties - Zixiang Dai; Jiali An; Xiaofeng Huang (BMC Oral Health)
Abstract Background Three-dimensional (3D) printed denture base resin exhibits limitations including low wear resistance, poor strength, and the lack of antimicrobial property. This study investigated the mechanical and antimicrobial properties of arginine-loaded mesoporous silica nanoparticles (Arg@MSNs) modified 3D-printed denture resin. Methods Arg@MSNs were synthesized, characterized, and incorporated into resin matrix at 0.5, 1.0, and 2.5 wt%, unmodified resin was served as control. Specimens were fabricated according to test specifications. Surface roughness (Ra), color alteration (ΔE), flexural strength/modulus, hardness and antimicrobial efficacy against Streptococcus mutans and Candida albicans were assessed. Data were evaluated by one-way analysis of variance, followed by the Tukey honestly significant difference post hoc test, with a significance level set at 0.05. Results Results showed that Arg@MSNs exhibited sustained arginine release and nanoscale morphology. The 2.5 wt% group demonstrated the highest Ra and ΔE value, significantly higher than other groups (p < 0.05). Flexural strength and modulus significantly improved at 0.5 wt% and 1.0 wt% compared to the control (p < 0.05), but decreased at 2.5 wt%. Incorporation of Arg@MSNs at all levels increased hardness, significantly exceeding that of the control (p < 0.05). Antimicrobial performance significantly improved with higher concentrations of Arg@MSNs. Conclusions The addition of 1.0 wt% Arg@MSNs imparted synergistic enhancements in antimicrobial efficacy and mechanical properties to the 3D-printed nanocomposite, while maintaining clinically acceptable surface roughness and aesthetic performance. These findings demonstrated that Arg@MSNs modified 3D-printed nanocomposite denture base resin, by combining 3D-printed resin with nanotechnology, has promising potential for functionalized dental prostheses.